Dynamic Stability and Changes in International Monetary Regimes - Aglietta, Michel (1992)
In this paper the author discusses the dynamics of the international monetaryregimes. In opposition to mainstream economics, these regimes are seen as irreversible historicalinstitutions characterized by a structural instability. They are defined by the degree ofexchange rate rigidity, by the mobility of capitals, and by weight of internal objectives in thepreference function of governments. Their dynamics is based on an irreversible sequence definedby the increasing degradation of macroeconomic adjustments, leading to the accumulationof tensions and to a structural instability, as the world economy changes, and finallyto questioning the founding principles of the international monetary regime. JEL Classification: E58; E42; F33; F36.